3x+14x-5=0

Simple and best practice solution for 3x+14x-5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+14x-5=0 equation:


Simplifying
3x + 14x + -5 = 0

Reorder the terms:
-5 + 3x + 14x = 0

Combine like terms: 3x + 14x = 17x
-5 + 17x = 0

Solving
-5 + 17x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 17x = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 17x = 0 + 5
17x = 0 + 5

Combine like terms: 0 + 5 = 5
17x = 5

Divide each side by '17'.
x = 0.2941176471

Simplifying
x = 0.2941176471

See similar equations:

| 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 | | 77-3x=33x+17 | | t+3+8(5+t)= | | X+6=0.5X-2 | | 11-9x=61-44x | | 3-28=5a | | 2x+35=5x+12 | | -114-8x=9x+22 | | 4(2X-7)=0 | | 9+5(t+1)+4t= | | 3x+7=-59-9x | | 10(2X-3)=8X | | 7(t+9)+5+t= | | 8t+(7+3t)4+2t= | | 4(X-1)=3(1-X) | | 7+9x=63+x | | 8t+7(7+3t)4+2t= | | 4x+30=11x-40 | | 11-7x=176-42x | | 4t+9+(2t+7)6= |

Equations solver categories